Application of Atmospheric Solids Analysis Probe Mass Spectrometry for the Taxonomic Analysis of Pollen - Latinovic, Adelina; Nichols, David S.; Adams, Vanessa M.; McQuillan, Peter B. (Frontiers in Ecology and Evolution, 2021)
Globally, both managed and wild pollination services are unable to meet current rates of crop production and pollination demand. Wild pollination services could be improved through the reforestation of agricultural land margins, however plant-pollinator networks remain poorly understood and the collection of key floral traits a complex process. Herein, we consider the merits of pollen as a floral trait and the application of a rapid pollen comparison method in assessing whether pollen traits are conserved at a taxonomic level. Reporting the previously unstudied, pollen fingerprints of 18 Australian plant species, we compare these against the seed crop Daucus carota L. and two naturalised Brassica hybrids. Applying atmospheric solids analysis probe – mass spectrometry (ASAP-MS) for rapid pollen fingerprinting, we compare pollens through non-metric multidimensional scaling (NMDS), Jaccard index correlation and hierarchical clustering. Demonstrating the merits of this analytical method for the grouping of potential revegetation flora, we identify key pollen similarities and differences that could correlate with wild pollinator preferences.